2008
DOI: 10.1111/j.1447-0349.2008.00545.x
|View full text |Cite
|
Sign up to set email alerts
|

Nursing handover within mental health rehabilitation: An exploratory study of practice and perception

Abstract: Nursing handover is an established practice that involves an interchange of information between nurses to inform of the condition of patients. It is essential to nursing practice in terms of continuity and quality of patient care. However, there is a lack of agreement about the quality, content, and process of handover and, in particular, a lack of information specific to mental health contexts. This paper reports the results of exploratory research of the practice and beliefs about verbal nursing handover wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 40 publications
0
30
1
Order By: Relevance
“…This transfer of information creates continuity and allows incoming nurses to make decisions about priorities and plan the provision of patient care during the shift (Strople & Ottani, ). Internationally, handover communication is an important aspect of providing safe patient care, yet researchers have suggested that handover communication is often incomplete and/or inaccurate (Kerr, Lu, McKinlay, & Fuller, ; McCloughen, O'Brien, Gillies, & McSherry, ; Meissner et al., ; Ong, Biomede, & Coiera, ). It has been documented that poor quality or ineffective shift handover can result in negative consequences for patients, staff and healthcare organizations (Australian Council for Safety and Quality in Health Care, , Drach‐Zahavy & Hadid, ; Kitch et al., ; Meissner et al., ; Moon, Gonzales, Woods, & Fox, ).…”
Section: Introductionmentioning
confidence: 99%
“…This transfer of information creates continuity and allows incoming nurses to make decisions about priorities and plan the provision of patient care during the shift (Strople & Ottani, ). Internationally, handover communication is an important aspect of providing safe patient care, yet researchers have suggested that handover communication is often incomplete and/or inaccurate (Kerr, Lu, McKinlay, & Fuller, ; McCloughen, O'Brien, Gillies, & McSherry, ; Meissner et al., ; Ong, Biomede, & Coiera, ). It has been documented that poor quality or ineffective shift handover can result in negative consequences for patients, staff and healthcare organizations (Australian Council for Safety and Quality in Health Care, , Drach‐Zahavy & Hadid, ; Kitch et al., ; Meissner et al., ; Moon, Gonzales, Woods, & Fox, ).…”
Section: Introductionmentioning
confidence: 99%
“…Handovers can include discussion of personal characteristics of the patient such as behavioural aspects (Liukkonen 1993). Some handovers have a structure that allows for the identification of the patients, their pathology and changes (Lamond 2000), whereas some aspects might be put aside in other settings (McCloughen et al. 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies addressed specific items that were missing in handovers, i.e. reason for admission [30,33], clinical condition/active medical problem [22,28,30,40], medication and other treatments [22,23], to-dos and care plan [27][28][29]40], in particular initiated but not yet completed tasks [30,33,35], the rationale of the task or the plan [27] and knowledge items [26]. Other studies summarized these items under "factual patient information" [27] or "detailed personal information" [33], which had to be up-to-date at the time of transmission [35].…”
Section: Types Of Errorsmentioning
confidence: 99%
“…Other studies summarized these items under "factual patient information" [27] or "detailed personal information" [33], which had to be up-to-date at the time of transmission [35]. However, it was also criticized that handovers were dominated by retrospective facts [33], lacked information on disagreement [27] and particularly lacked anticipatory guidance or recommendations [25,[28][29][30]35].…”
Section: Types Of Errorsmentioning
confidence: 99%